ENDOCRINE TUMOURS: Imaging in the follow-up of differentiated thyroid cancer: current evidence and future perspectives for a risk-adapted approach. Issue 5 (November 2016) - Lamartina, Livia; Deandreis, Désirée; Durante, Cosimo; Filetti, Sebastiano
Abstract : The clinical and epidemiological profiles of differentiated thyroid cancers (DTCs) have changed in the last three decades. Today's DTCs are more likely to be small, localized, asymptomatic papillary forms. Current practice is, though, moving toward more conservative approaches (e.g. lobectomy instead of total thyroidectomy, selective use of radioiodine). This evolution has been paralleled and partly driven by rapid technological advances in the field of diagnostic imaging. The challenge of contemporary DTCs follow-up is to tailor a risk-of-recurrence-based management, taking into account the dynamic nature of these risks, which evolve over time, spontaneously and in response to treatments. This review provides a closer look at the evolving evidence-based views on the use and utility of imaging technology in the post-treatment staging and the short- and long-term surveillance of patients with DTCs. The studies considered range from cervical US with Doppler flow analysis to an expanding palette of increasingly sophisticated second-line studies (cross-sectional, functional, combined-modality approaches), which can be used to detect disease that has spread beyond the neck and, in some cases, shed light on its probable outcome.